2017
DOI: 10.1177/1359105317740620
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and life satisfaction in drug addicts: Self-esteem and loneliness as mediators

Abstract: This study was designed to investigate the mediation effects of both self-esteem and loneliness on the relationship between social support and subjective well-being in drug addicts. In all, 110 participants, all drug addicts from Guangdong Fangcun Brain Hospital, completed the questionnaire. Pearson's correlation analysis showed that perceived social support was positively related to self-esteem and life satisfaction and was negatively correlated with loneliness in drug addicts. Structural equation modeling es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Perceived social support was found to be significantly correlated with psychological distress and satisfaction with life; in particular, the family, friends, and significant other subscales of the MSPSS were reported to be negatively correlated with psychological distress and positively correlated with satisfaction with life. Another study conducted with individuals with drug addiction revealed a positive correlation between social support and satisfaction with life [20]. Social support helps reduce problematic behaviors, thus enhancing their adjustment and reducing adverse effects on their psychological state [21].…”
Section: Discussionmentioning
confidence: 99%
“…Perceived social support was found to be significantly correlated with psychological distress and satisfaction with life; in particular, the family, friends, and significant other subscales of the MSPSS were reported to be negatively correlated with psychological distress and positively correlated with satisfaction with life. Another study conducted with individuals with drug addiction revealed a positive correlation between social support and satisfaction with life [20]. Social support helps reduce problematic behaviors, thus enhancing their adjustment and reducing adverse effects on their psychological state [21].…”
Section: Discussionmentioning
confidence: 99%
“…Social anxiety was positively associated with loneliness, and these two variables also strongly and negatively predicted life satisfaction. In addition, loneliness has also been considered as a mediator in the relationship between several intrapersonal variables (e.g., perceived social support and core self‐evaluation) and life satisfaction (Cao & Liang, ; He, Shi, & Yi, ; Rijken & Groenewegen, ). The research conducted by Cao and Liang () had suggested a partially mediating effects of loneliness in the links from perceived social support to life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, loneliness has also been considered as a mediator in the relationship between several intrapersonal variables (e.g., perceived social support and core self‐evaluation) and life satisfaction (Cao & Liang, ; He, Shi, & Yi, ; Rijken & Groenewegen, ). The research conducted by Cao and Liang () had suggested a partially mediating effects of loneliness in the links from perceived social support to life satisfaction. Similarily, with two groups of Chinese adolescent He et al () found that loneliness partially mediated the relationships between core self‐evaluation and life satisfaction, as well as the impact of affect on life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that social support is an important indicator of life satisfaction in numerous studies among different population groups including the elderly (Gow, et al, 2007), prisons officers (Onyishi, Okongwu, & Ugwu, 2012), undergraduate students (Kong, Ding, & Zhao, 2015), and drug addicts (Cao & Liang, 2017). Social support usually refers to assistance and support of both a mental or physical nature that is provided by numerous groups of society, including parents, relatives, and friends (Hyde, Gorka, Manuck, & Hariri, 2011; Zhang, Zhang, Yang, & Li, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…For example, Kong and You (2013) demonstrated that loneliness and self-esteem had a mediating effect on the association of social support with post-adolescent youth’s life satisfaction. Cao and Liang (2017) revealed that perceived social support could influence life satisfaction partially via self-esteem and loneliness. Kong, Zhao, and You (2013) found evidence of a moderating effect of social support and subjective well-being.…”
Section: Introductionmentioning
confidence: 99%